The number of involved regions by prostate adenocarcinoma predicts histopathology concordance between radical prostatectomy specimens and MRI/ultrasound-fusion targeted prostate biopsy - Igor Yusim; Elad Mazor; Einat Frumkin; Ben Hefer; Sveta Li; Victor Novack; Nicola J. Mabjeesh (Frontiers in Oncology)
IntroductionThe prostate biopsy (PB) results should be concordant with prostatectomy histopathology to avoid overestimating or underestimating the disease, leading to inappropriate or undertreatment of prostate cancer (PCa) patients. Since the introduction of multiparametric Magnetic Resonance Imaging (mpMRI) in the diagnostic pathway of PCa, most studies have shown that MRI/Ultrasound fusion-guided (MRI-fusion) PB improves concordance with histopathology of radical prostatectomy specimens. This study aimed to evaluate the improvement in concordance of prostatectomy specimens with PB histopathology obtained using the MRI-fusion approach compared with the 12-core TRUS-Bx and to identify the variables influencing this.Patients and methodsThe study included 218 men who were diagnosed with PCa by PB and underwent radical prostatectomy between 2016 and 2023. The patients were grouped based on the biopsy method: 115 underwent TRUS-Bx, and 103 underwent MRI-fusion PB. The histopathological grading of these biopsy approaches was compared with that of radical prostatectomy specimens. Multivariate logistic regression analyses were conducted to evaluate the impact of various criteria on histopathological concordance.ResultsIn patients with unfavorable intermediate- and high-risk PCa, MRI-fusion PB showed significantly better concordance with prostatectomy histopathology than TRUS-Bx (73.1% vs. 42.9%, p = 0.018). MRI-fusion PB had a significantly lower downgrading of prostatectomy histopathology than TRUS-Bx in all grade categories. The number of cancer-involved regions of the prostate is an independent predictor for concordance (OR = 1.24, 95%CI = 1.04-1.52, p = 0.02) and downgrading (OR = 0.46, 95%CI = 0.24-0.83, p = 0.01).ConclusionsUsing an MRI-fusion PB improves histopathological concordance in patients with unfavorable intermediate and high-risk PCa. It reduces the downgrading rate of prostatectomy histopathology compared with TRUS-Bx in all grade categories. The number of cancer-involved regions is an independent predictor of the concordance between biopsy and final histopathology after prostatectomy and post-prostatectomy histopathology downgrading. Our findings could assist in selecting PCa patients for AS and focal treatment based on the histopathology obtained from the MRI-fusion PB.